A childhood-onset rapid-onset dystonia parkinsonism family with ATP1A3 gene mutation and literatures review - Zhang, C L (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2017)
Objective: To explore clinical characteristics, treatment, and prognosis of a family with childhood-onset rapid-onset dystonia parkinsonism (RDP) caused by ATP1A3 gene mutation and review literatures. Method: The clinical data of a RDP child, his brother and mother had been analyzed retrospectively. This family was admitted to Xiangya Hospital in January 2016. DNA samples were analyzed by the next-generation sequencing and confirmed by Sanger sequencing. Related literature from PubMed, Online Mendelian Inheritance in Man (OMIM), CNKI and Wanfang databases to date (up to October 2016) with"Rapid-onset dystonia-parkinsonism""RDP""DYT12" as key words was reviewed. Result: The proband boy was three years and four months old (April 2015) when he had the first attack of the disease. After a febricity, he suddenly acquired acute aphasia and limb movement disorder. Rehabilitation therapy and supportive treatment made his speech gradually recovered but still slurred. However, his abnormal walking posture still existed. Nine months later (January 2016, 4 years and one months old), symptoms including aphasia, dysphagia, and weakness with rostrocaudal gradient reoccured after fever. The disease progressed to the critical condition within 24 hours. He"seizured" four times with tonic spasms of limbs but without loss of consciousness. Family history showed his grandparents were consanguineous marriage. His mother and brother also developed abnormal gait and dysarthria after an infection before primary school age. Their symptoms improved gradually without relapsing. However, they did not recover entirely with mild intellectual disability. His mother had a healthy brother and sister. This proband had no other siblings but the brother. Heterozygous missense mutation p. R756H in ATP1A3 gene was detected in this proband, his mother and his brother. This mutation had been reported pathogenically related to RDP, and it located in highly conserved gene region. Benzodiazepine was used for the proband and his brother, with the proband being improved better although not completely. Meanwhile, benzodiazepine had no significant effect on his mother because of poor compliance. This is the first case report of RDP in China. The mutations of ATP1A3 have been previously reported in 51 patients including 6 large families and 16 other unrelated patients. A total of 14 different mutations in ATP1A3 gene with RDP have been reported to date, including 12 missense mutations, a 3-bp in-frame deletion, and a 3-bp in-frame insertion. The sporadic cases all had the typical clinical phenotypes of RDP, such as the abrupt onset of dysarthria, dysphagia, limb dystonia with bradykinesia, and postural instability. The symptoms of bulbar and arms were much more obvious. It was hard to diagnose RDP in a family because some patients had typical symptoms of RDP, while the others might experience from mild symptoms to no symptoms, which might be related to incomplete penetrance of RDP. Two cases carrying the same mutation as our patients also presented some overlapping phenotypes. Conclusion: The p. R756H heterozygous mutation in ATP1A3 gene is the pathogenic mutation of RDP, analysis of genotype-phenotype correlations of RDP will be very important and meaningful